Effects of Pictorial Integrated Technology and Cooperative Learning Strategies on Pupils’ Academic Performance in Social Studies in Katsina State, Nigeria - Aguh, Justina Chinyere; Komolafe, Adefunke Titilayo; Sopekan, Oludola Sarah (FKIP Universitas Lampung, 2023)
Social Studies is a problem- solving subject taught in early childhood classroom but it is faced with challenges of inappropriate instructional strategies and pupil’s poor academic performance. The use of teacher centred instructional strategies in teaching of Social Studies have to led to low level of pupil’s retention, boredom, lack of interest and relatively poor academic performance. The objective of this study was to investigate the effects of Pictorial integrated technology and cooperative learning strategies on pupil’s academic performance in Social Studies. Five hypotheses were raised for the study. The study adopted pre-test and posttest quasi experimental design with one hundred and twenty (120) basic two pupils which consists Sixty- two (62) Males and Fifty- Eight (58) Females. Probability sampling technique was used to select three (3) Basic two schools in Malumfashi Zonal Inspectorate in Katsina State. Social Studies Performance Test, Pictorial Integrated Technology Social Studies Questionnaire and Cooperative Learning Strategy Social Studies Questionnaire were developed by the researchers. Social Studies Performance Test yielded a reliability of 0. 92 while Pictorial Integrated Technology Social Studies Questionnaire and Cooperative Learning Strategy Social Studies Questionnaire yielded a correlation index of 0.73 and 0.75 respectively. The data were analyzed using descriptive statistics and Analysis of Covariance (ANCOVA) at 0.05 level of significance It was deducted that pictorial integrated technology and cooperative learning strategies enhance pupil’s academic performance in Social Studies when effectively utilized in the classroom. Based on the findings of the study, the researchers concluded that pictorial integrated technology and cooperative learning strategies has more effects on basic two pupils’ academic performance in Social Studies than lecture method. Further study could be carried out to determine the effects of pictorial integrated technology and cooperative learning strategies on pupils ‘achievement and retention of Social Studies concepts for easy generalization.Key Words: Pictorial, integrated technology, cooperative learning strategy, pupils, Social Studies,DOI: http://dx.doi.org/10.23960/jpp.v13.i1.202306